THE EFFICIENCY OF INFORMATION FROM FINANCIAL STATEMENTS - منيسي احمد (Dirasat in Economics and Business, 1975)
According to article 572 of the Libyan Commercial Law, the manager of stock companies should prepare the annual financial statements of the company including profit and loss account, in a way that it clearly and accurately reflects the financial position of the company' enclosed with a detailed financial report. Although the Law does not oblige the management to publish the information to the public, it indicates the necessity of making the statement and report available to the shareholder at the headquarters of the company for fifteen days.